A novel colistin adjuvant identified by virtual screening for ArnT inhibitors. (8th June 2020) - Ghirga, Francesca; Stefanelli, Roberta; Cavinato, Luca; Lo Sciuto, Alessandra; Corradi, Silvia; Quaglio, Deborah; Calcaterra, Andrea; Casciaro, Bruno; Loffredo, Maria Rosa; Cappiello, Floriana; Morelli, Patrizia; Antonelli, Alberto; et al.
Abstract: Background: Colistin is a last-resort treatment option for many MDR Gram-negative bacteria. The covalent addition of l- aminoarabinose to the lipid A moiety of LPS is the main colistin resistance mechanism in the human pathogen Pseudomonas aeruginosa . Objectives: Identification (by in silico screening of a chemical library) of potential inhibitors of ArnT, which catalyses the last committed step of lipid A aminoarabinosylation, and their validation in vitro as colistin adjuvants. Methods: The available ArnT crystal structure was used for a docking-based virtual screening of an in-house library of natural products. The resulting putative ArnT inhibitors were tested in growth inhibition assays using a reference colistin-resistant P. aeruginosa strain. The most promising compound was further characterized for its range of activity, specificity and cytotoxicity. Additionally, the effect of the compound on lipid A aminoarabinosylation was verified by MS analyses of lipid A. Results: A putative ArnT inhibitor (BBN149) was discovered by molecular docking and demonstrated to specifically potentiate colistin activity in colistin-resistant P. aeruginosa isolates, without relevant effect on colistin-susceptible strains. BBN149 also showed adjuvant activity against colistin-resistant Klebsiella pneumoniae and low toxicity to bronchial epithelial cells. Lipid A aminoarabinosylation was reduced in BBN149-treated cells, although only partially. Conclusions: This study demonstrates that in silico screening targeting ArnT can successfully identify inhibitors of colistin resistance and provides a promising lead compound for the development of colistin adjuvants for the treatment of MDR bacterial infections.